Half-sandwich lanthanide crown ether complexes with the slow relaxation of magnetization and photoluminescence behaviors. Issue 4 (10th January 2017) - Gao, Feng; Yang, Feng-Lei; Feng, Xiaowan; Xu, Huimin; Sun, Wang; Liu, Huan; Li, Xiu-Ling
Abstract : Four half-sandwich lanthanide crown ether complexes were successfully synthesized and structurally characterized. Dysprosium complexes show both the slow relaxation of magnetization and photoluminescence behaviors. Abstract : Four half-sandwich type mononuclear lanthanide crown ether complexes with the formula [Ln(12-crown-4)(NO3 )3 ] (Ln 3+ = Dy 3+ (1 ), Tb 3+ (2 ), Ho 3+ (3 ), and Er 3+ (4 ); 12-crown-4 = 1, 4, 7, 10-tetraoxacyclododecane) were successfully synthesized and structurally characterized. Ac magnetic susceptibility measurements reveal that dysprosium complex1 behaves as a typical single-ion magnet, while solid state photoluminescence studies show that complexes1 and2 have the respective lanthanide(iii ) luminescence characteristics.